Contemporary ethnic minority entrepreneurship in the UK: A quantitative exploration of break out and entrepreneurial quality. Issue 7 (11th November 2019) - Daniel, Elizabeth; Henley, Andrew; Anwar, Muhammad Naveed
Abstract : Purpose: Ethnic minority entrepreneurs (EMEs) are traditionally associated with lower growth industry sectors. The purpose of this paper is to draw on the theory of mixed embeddedness to determine if more recent EMEs have been able to break out of lower growth sectors and if break out varies across ethnic minority groups. It also compares entrepreneurial quality in terms of weekly hours worked, weekly earnings and job satisfaction. Design/methodology/approach: Quantitative inferential statistical analysis is undertaken on data drawn from the large scale, social sciences data set for the UK, Understanding Society. Findings: The study finds that break out is not associated with being a recent EME but does vary across ethnic minority groups. Break out is found to be associated with gender, education, English language proficiency and occupational status. Some variation in entrepreneurial quality is found for both recent EMEs and across ethnic minority groups. Practical implications: Understanding the nature and quality of ethnic minority entrepreneurship is important since it informs public debate about migration, informs policy and shapes activities of future EMEs. Originality/value: The study provides a theoretically grounded interpretation of the explanatory variables associated with EME break out and entrepreneurial quality. Second, it provides a large confirmatory study of break out and finally, it also finds an important empirical nuance to the concept of opportunity structure by identifying a variation over time in both external and socio-demographic factors.